2015
DOI: 10.1177/0972063415575819
|View full text |Cite
|
Sign up to set email alerts
|

Age at Marriage

Abstract: Age at marriage' is not only a crucial but also a decisive variable in limiting family size and fertility level. There is an inverse correlation between age at marriage and fertility level. If age at marriage increases, fertility level would decline. In order to examine this relationship, the present study has collected data from households of Yerava tribe in Kodagu district of Karnataka. A sample of 10 tribal colonies was selected on the basis of a stratified sampling procedure. A total of 250 households were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several studies have identified the negative impact that early age at marriage and early childbearing have on maternal and child health (Marphatia et al 2017;Prabhuswamy, 2015;Santhya et al, 2010). The age at marriage, more particularly for girls, was found to be very low among the tribal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified the negative impact that early age at marriage and early childbearing have on maternal and child health (Marphatia et al 2017;Prabhuswamy, 2015;Santhya et al, 2010). The age at marriage, more particularly for girls, was found to be very low among the tribal communities.…”
Section: Discussionmentioning
confidence: 99%